Sea Lavender (Heliotropium gnaphalodes L.): Identification and Uses - Stephen H. Brown; Marc S. Frank; Andrew K. Koeser (EDIS, 2018)
Sea lavender is a native plant found naturally along the Atlantic coast of central and south Florida. This 7-page document discusses this species’ identification and uses. Written by Stephen H. Brown, Marc S. Frank, and Andrew K. Koeser and published by the UF/IFAS Environmental Horticulture Department, August 2018. http://edis.ifas.ufl.edu/ep563